The effect of nordihydroguaiaretic acid, an inhibitor of prostaglandin and leukotriene biosynthesis, on hematopoiesis of gamma-irradiated mice - Kozubík, A; Hofmanová, J; Holá, J; Netíková, J (Experimental hematology, 1993)
The effects of the inhibition of the cyclooxygenase and lipoxygenase metabolic pathways of arachidonic acid on the postirradiation recovery of hematopoietic functions in mice were investigated. Nordihydroguaiaretic acid (NDGA), an inhibitor of prostaglandin (PG) and leukotriene (LT) production, was given to animals in single doses (0.015 to 0.75 mg/mouse) 1 hour before 5 Gy of total-body gamma-irradiation. Enhanced hematopoietic recovery in terms of exogenous and endogenous spleen colonies, femoral granulocyte-macrophage colony-forming cells and peripheral blood granulocyte levels was observed at higher doses of NDGA. The treatment used influenced neither lymphocyte nor erythrocyte postirradiational levels or hemoglobin concentration. A comparison of the effects induced by a high dose of NDGA (0.3 mg per mouse) with those observed after an isomolar dose of indomethacin (an inhibitor of PG production) indicated only slight differences between these two drugs. An isomolar dose of esculetin (an inhibitor of LT production) had no effect on the postirradiation behavior of hematopoiesis. The results suggest that the inhibition of PG production plays the main role in the mechanism of NDGA action. Inhibition of LT production seems to be of less importance for hematopoiesis in these in vivo conditions.
Keywords: záření gama; Animals; Gamma Rays; Leukotrienes; umbeliferony; slezina; makrofágy; Whole-Body Irradiation; kyselina nordihydroguaiaretová; indomethacin; antagonisté leukotrienů; Masoprocol; Indomethacin; Macrophages; Mice; prostaglandiny; Umbelliferones; myši; Prostaglandins; Hematopoiesis; leukotrieny; Prostaglandin Antagonists; Leukotriene Antagonists; Male; myši inbrední C57BL; granulocyty; Mice, Inbred CBA; Spleen; Granulocytes; hematopoéza; antagonisté prostaglandinu; zvířata; mužské pohlaví; myši inbrední CBA; Mice, Inbred C57BL; celotělové ozáření